Etanercept for patients with juvenile idiopathic arthritis: drug levels and influence of concomitant methotrexate: observational study - Levälampi Tiina; Kärki Johanna; Rebane Katariina; Vähäsalo Paula; Malin Merja; Kröger Liisa; Grönlund Minna-Maija; Backström Maria; Pohjankoski Heini; Kautiainen Hannu; Jokiranta Sakari; Aalto Kristiina (BMC, 2025)
Background: Etanercept (ETN) is widely used tumour necrosis factor (TNF) blocker in the treatment of juvenile idiopathic arthritis (JIA) when traditional synthetic disease modifying antirheumatic drug (sDMARD) therapy is not sufficient. There is limited information about the effects of methotrexate (MTX) on serum ETN concentration in children with JIA. We aimed to investigate whether ETN dose and concomitant MTX would effect ETN serum trough levels in JIA patients, and whether concomitant MTX have an influence on the clinical response in patients with JIA receiving ETN.
Methods: In this study, we collected the medical record data of 180 JIA patients from eight Finnish pediatric rheumatological centres. All these patients were treated with ETN monotherapy or combination therapy with DMARD. To evaluate the ETN concentrations, blood samples of the patients were collected between injections right before the subsequent drug. Free ETN level was measured from serum.
Results: Ninety-seven (54%) of the patients used concomitant MTX, and 83 (46%) received either ETN monotherapy or used sDMARDs other than MTX. A significant correlation was noted between ETN dose and drug level [r = 0.45 (95% CI: 0.33-0.56)]. The ETN dose and serum drug level were correlated (p = 0.030) in both subgroups - in MTX group [r = 0.35 (95% CI: 0.14-0.52)] and in non-MTX group [r = 0.54 (95% CI: 0.39-0.67)].
Conclusion: In the present study, we found that concomitant MTX had no effect on serum ETN concentration or on clinical response. In addition, a significant correlation was detected between ETN dose and ETN concentration.